Avaliação do ensino e grau de conhecimento de conteúdos de geriatria e gerontologia de acadêmicos de cursos de medicina brasileiros - Bonilla, José Maurício Vieira (2017)
Medical programs are training general practitioners, based on education and infrastructure systems that do not follow the biopsychosocial demands of the human aging process. The purpose of this research was to evaluate education and degree of knowledge of geriatrics and gerontology (GG) topics in students from medical programs of Higher Education Institutions in Brazil. The research is a cross-sectional study. Data was collected through the application of a self-administered online questionnaire and analyzed using R language. Student's t test and Fisher's exact test were applied for evaluation of the studied factors considering education and the degree of knowledge. Significance level p ≤ 0.05 was applied for statistical inference. Of the 335 respondents, 123 (36.7%) indicated to have knowledge about geriatrics giants and 212 63.3%) indicated they did not have knowledge of the subject. Results showed medical students have modest knowledge of the main topics included in geriatrics and gerontology. New studies on the subject should be executed to better delineate the education process developed on GG in Brazilian medical programs.